ANALISIS FAKTOR KINERJA BIDAN TERHADAP PELAYANAN KEBIDANAN CONTINTY OF CARE DI TPMB - Fatmawati, Istiadah; Hidayati, Nurul (LPPM STIKES HUSADA JOMBANG, 2023)
Bacground: The concept of Continuity of Care is a service that covers the time from before pregnancy, pregnancy, delivery, and after delivery. The implementation of this service is related to the performance of a midwife. The performance of midwives can be influenced by internal factors, namely education, training, attitudes, motivation, length of service, knowledge and skills. There are 30 Midwife independent practice throughout Sidoarjo City that have made an MoU with PC IBI Sidoarjo City, but there are still midwives who have not provided Continuity of Care, one of which is due to the large influence of internal midwife factors. Purpose: The purpose of this study is to know the internal factors that affect the performance of midwives in providing Continuity of Care. Methods: This type of research is quantitative with the design of this study is